1996
DOI: 10.1159/000267957
|View full text |Cite
|
Sign up to set email alerts
|

UV-B-lnduced Cataract Model in Brown-Norway Rat Eyes Combined with Preadministration of Buthionine Sulfoximine

Abstract: In order to develop a more adequate ultraviolet (UV)-induced cataract model, a combination of /-buthionine sulfoximine (BSO) treatment was applied to experimental animals. A single administration of BSO 4 mmol/ kg caused reduced glutathione concentration until experimental day 8. In the 0.067-J/cm2 UV-B irradiation experiment, the light-scattering intensity of the anterior lens cortex of the combination group was significantly higher than that of the other groups during the second week after irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…We chose a total dose of UV-B irradiation equal to the single exposure dose that had been used in a rat cata ract model [5], But comparing with a human lens, the intensity of UV-B in the present work was much higher than that which might reach to a human lens [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose a total dose of UV-B irradiation equal to the single exposure dose that had been used in a rat cata ract model [5], But comparing with a human lens, the intensity of UV-B in the present work was much higher than that which might reach to a human lens [18].…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet B (UV-B) has been considered as a cataractogenesis factor in epidemiological studies and in animal experiments [1][2][3][4][5]. The most probable way that UV-B causes damage to the lens is photooxidation, but details of the mechanisms remain obscure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study also showed that total doses of UV-B above 1000 mJ/cm 2 are required to induce cataractogenesis. 7 All rats in this study were exposed to a dose of UV-B once a week, which started at 100 mJ/cm 2 and was gradually increased fi rst to 150 and fi nally to 200 mJ/cm 2 after weekly confi rmation, 1 day before exposure of the absence of corneal opacities by slit-lamp microscopy. The mechanisms of UV-B-induced cataract formation have been speculated to include a number of factors such as production of reactive oxygen species, 18 DNA damage as strand breaks and fragmentation in lens epithelial cells, 19,20 formation of DNA photoproducts, 21 apoptosis 19,20 of lens epithelial cells and subsequent formation of stratifi ed epithelial cells, lower activity of the defense mechanism superoxide dismutase, increment of lipid peroxide, and hypofunction of the capacity to repair damage.…”
Section: Discussionmentioning
confidence: 99%
“…The light-scattering intensities (LSIs) of the anterior subcapsular and nuclear layers were evaluated using software interfaced with the EAS-1000, which was developed by Sasaki et al 7 Ocular surfaces were examined by slit-lamp microscopy with fl uorescein staining (5 μl, 0.5% solution).…”
Section: Observation and Documentation Of Lenticular Changes And Oculmentioning
confidence: 99%